The effect of female genital mutilation on couple sexual function - A. Abdel Raheem, Talal; M. R. El-tahalawi, Samar; M. Abo Raia, Nesreen; Younis Elsary, Asmaa; Mahmoud Ibrahem, Kairman (International Journal Of Community Medicine And Public Health, 2018)
Background: Female genital mutilation (FGM) is a procedure that had physical, social, psychological, and sexual complications. The study aimed to assess effect of FGM on couple sexual function. Methods: case control nested from cross-sectional study in Fayoum governorate; it was conducted during a period of five months (March 2016 to July 2016). Results: The prevalence of FGM was 432(83.4%). The risk of exposure to mutilation was about four folds higher among women inhabitant rural areas, and about nine folds higher among low educated women, and around six folds higher if parents were low educated. Around one-third of women in the study 157 (30.3%) suffered psychological problems and 142 (27.4%) of them suffered marital and social problems related to FGM practice. Mutilated women had five folds decrease in desire: four folds decrease in sexual satisfaction and five folds increase in sexual dysfunction on contrary 57% to 59% decrease in arousal and orgasm. As regards to husband sexual satisfaction, it decreases by around three folds if their wives were mutilated. There is statistically a significant increase in couple sexual dysfunction among complicated mutilation. Conclusions: FGM is still practiced in Egypt and it resulted in many physical, psychological, and social complications; also it had a negative impact on the couple’s sexual life.